Glass ceramic and preparation method thereof, cover plate glass and electronic equipment
By controlling the surface roughness and edge chamfer structure of microcrystalline glass, and combining chemical reinforcement treatment, the problem of insufficient bending performance of microcrystalline glass is solved, significantly improving its bending performance and life, and is suitable for applications such as folding screens.
Patent Information
- Application Number
- CN202411593900.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2024-12-31
AI Technical Summary
Existing microcrystalline glass has shortcomings in bending performance and bending life, especially the small ultimate bending radius and limited number of bending times, resulting in poor performance in applications such as folding screens.
By controlling the surface roughness and edge chamfer structure of ultra-thin microcrystalline glass, ensure that the surface roughness is within a specific range, and forming a structure with specific arc chamfer during edge treatment, combined with chemical reinforcement treatment, improve microcrystalline glass bending performance and lifespan.
It significantly improves the bending performance and bending life of microcrystalline glass, making it better perform in applications such as folding screens, with the ultimate bending radius increasing and the number of dynamic bending times increasing.
Smart Images

Figure CN119219335A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of microcrystalline glass, and in particular to a microcrystalline glass with high bending performance and a preparation method thereof, a cover glass and an electronic device. Background Art
[0002] As an important component of the folding screen, the cover plate needs to have excellent impact resistance, scratch resistance, deformation resistance, and bending resistance. At present, common materials for folding screen cover plates include colorless polyimide (CPI), high temperature resistant polyester (PET), ultra-thin glass (UTG) and ultra-thin microcrystalline glass (microcrystalline UTG). Among them, CPI and PET are prone to whitening of creases, insufficient surface scratch resistance, and poor touch after bending. Due to its extremely thin nature, UTG is still easy to break even after strengthening treatment, and has poor impact resistance. Microcrystalline UTG has better hardness, scratch resistance, impact resistance, deformation resistance, drop resistance, anti-scattering and other properties, and has broad application prospects in folding screen cover materials.
[0003] However, since the microcrystalline glass on the market generally has high brittleness and Young's modulus, the microcrystalline UTG obtained by thinning it is very likely to have insufficient bending performance, such as: (1) large limit bending radius; (2) short bending life in conventional scenarios, etc. The inventors found that even if the existing mature UTG production process is used to make the existing microcrystalline glass into microcrystalline UTG, the limit bending radius of the obtained microcrystalline UTG is only about 2.0mm to 5.0mm. When the bending life of the obtained microcrystalline UTG is tested, at R2.5 (bending radius 2.5mm), the number of bends is only less than or equal to 10,000 times.
[0004] It should be noted that this part of the present application only provides background technology related to the present application and does not necessarily constitute prior art or known technology. Summary of the invention
[0005] Without being bound by any theory, the inventors have found that, similar to ultra-thin glass (UTG), the edge chamfer structure of ultra-thin microcrystalline glass (microcrystalline UTG) also has a significant effect on its bending performance. The characteristics of the edge chamfer structure are very important for improving the bending performance and bending life of ultra-thin microcrystalline glass products. However, unlike ultra-thin glass (UTG), the bending performance and bending life of microcrystalline UTG cannot be improved to a higher range only by controlling the ratio of chamfer width a and chamfer height b, the ratio of chamfer width a and microcrystalline glass thickness t, and performing chemical strengthening treatment. The resulting microcrystalline UTG still has the problem of insufficient bending performance.
[0006] Furthermore, the inventors found that when preparing ultra-thin glass-ceramics, by making the surface roughness of the ultra-thin glass-ceramics as small as possible,
[0007] At the same time, during edge processing, the ultra-thin microcrystalline glass is formed into a chamfered structure with a specific edge shape, which is conducive to obtaining ultra-thin microcrystalline glass with better bending performance after chemical strengthening treatment.
[0008] The present application provides a microcrystalline glass, a cover glass and an electronic device comprising the microcrystalline glass. The microcrystalline glass is an ultra-thin microcrystalline glass, the roughness of its main surface meets a specific range, and it has an arc chamfer, and the edge curve of the chamfer meets a specific relationship / function, which is beneficial to reduce the risk of breakage due to edge stress concentration during bending, so that the microcrystalline glass has better bending performance and a higher bending life.
[0009] Specifically, the technical solutions provided by this application include:
[0010] In a first aspect, a microcrystalline glass is provided, the microcrystalline glass comprising a first main surface, a second main surface, and at least one side surface connecting the first main surface and the second main surface;
[0011] The surface roughness Ra of the first main surface and the second main surface satisfies: Ra≤150nm, preferably, Ra≤145nm, more preferably, Ra≤140nm;
[0012] In the microcrystalline glass, at least one of the side surfaces has at least one chamfer, the edge of the chamfer is arc-shaped, a coordinate system is established in a cross section perpendicular to the side surface along the thickness direction, the symmetry axis of the two main surfaces of the microcrystalline glass is taken as the x-axis, and the straight line passing through the chamfer starting point on the main surface and perpendicular to the x-axis is taken as the y-axis, and the edge curve of the chamfer satisfies the following relationship:
[0013]
[0014] Wherein, k satisfies 0.36≤k≤3.52, preferably, 0.36≤k≤3, and more preferably, 0.36≤k≤2.5, and t is the thickness of the microcrystalline glass, in mm.
[0015] The present application reduces the risk of breakage due to edge stress concentration during bending by making the surface roughness of the microcrystalline glass meet a specific range and making the edge of the microcrystalline glass form an arc chamfer that meets a specific relationship, so that the microcrystalline glass has better bending performance and a longer bending life. In the present application, the edge chamfer structure of the side surface of the microcrystalline glass can be formed by, but not limited to, chemical etching.
[0016] In some embodiments of the present application, the surface roughness Ra is 55nm to 140nm; and / or
[0017] In the relationship satisfied by the chamfered edge curve, the value of k is 0.36 to 2.08.
[0018] In some embodiments of the present application, the surface roughness Ra is 55 nm, 96 nm, 100 nm or 140 nm; and / or, in the relationship satisfied by the edge curve of the chamfer, the value of k is 0.36, 1.12, 1.69 or 2.08.
[0019] In some embodiments of the present application, the thickness t of the microcrystalline glass is 0.02 mm to 0.2 mm, preferably 0.02 mm to 0.1 mm, and more preferably 0.02 mm to 0.05 mm. In some embodiments of the present application, the thickness of the microcrystalline glass is 0.025 mm or 0.03 mm.
[0020] In some embodiments of the present application, in the glass-ceramic, at least one of the side surfaces has a first chamfer facing the first main surface and a second chamfer facing the second main surface, and the first chamfer and the second chamfer are substantially symmetrical on both sides of the glass-ceramic. Here, "substantially symmetrical" means that the edge chamfer structure of the glass-ceramic is substantially symmetrical with a horizontal line passing through the center point of the glass-ceramic as the axis of symmetry.
[0021] In some embodiments of the present application, at least two side surfaces in the length direction of the microcrystalline glass have the chamfers, and more preferably, four side surfaces of the microcrystalline glass have the chamfers, and preferably the chamfers include a substantially symmetrical first chamfer toward the first main surface and a second chamfer toward the second main surface. Such a chamfer structure is conducive to reducing the risk of breakage due to edge stress concentration during bending.
[0022] In some embodiments of the present application, the chamfer has a chamfer width a and a chamfer height b, and the chamfer width a and chamfer height b of the chamfer satisfy: 1≤a / b≤20, preferably, 1≤a / b≤10, and more preferably, 1.2≤a / b≤6. The width direction of the chamfer is the same as the extension direction of the main surface of the microcrystalline glass to the side surface, and the height direction of the chamfer is the same as the thickness direction of the microcrystalline glass. In the present application, by making the ratio of the chamfer width a and the chamfer height b of the chamfer satisfy a specific range, it is beneficial to form a specific chamfer edge shape, thereby reducing the risk of breakage caused by edge stress concentration during bending, so that the microcrystalline glass has better bending performance.
[0023] In some embodiments of the present application, a ratio a / b of a chamfer width a to a chamfer height b of the chamfer is 1.2, 3, 4.7 or 5.4.
[0024] In some embodiments of the present application, the chamfer width a of the chamfer and the thickness t of the glass-ceramics satisfy: 0.6≤a / t≤1.5, preferably: 0.6≤a / t≤1.4, and more preferably, 0.6≤a / t≤1.2. In the present application, by making the ratio of the chamfer width a of the chamfer and the thickness t of the glass-ceramics meet a specific range, it is beneficial to form a specific chamfer edge shape, which is beneficial to reduce the risk of breakage caused by edge stress concentration during the bending process, so that the glass-ceramics has better bending performance.
[0025] In some embodiments of the present application, a ratio a / t of a chamfer width a of the chamfer to a thickness t of the glass-ceramics is 0.6, 1, 1.1 or 1.2.
[0026] In some embodiments of the present application, the Young's modulus E of the microcrystalline glass is 80GPa to 130GPa, preferably 90GPa to 120GPa, and more preferably 95GPa to 115GPa. In the present application, an excessively high Young's modulus makes the microcrystalline glass more susceptible to brittle fracture when bent, and reduces the shaping ability of the microcrystalline glass, which is not conducive to obtaining excellent bending performance; but an excessively small Young's modulus is not conducive to the deformation resistance and impact resistance of the microcrystalline glass. Therefore, in order to take into account the bending performance, deformation resistance and impact resistance of the microcrystalline glass, the present application makes the Young's modulus E of the microcrystalline glass meet 80GPa to 130GPa.
[0027] In some embodiments of the present application, the Young's modulus E of the glass-ceramics is 98.8 GPa to 110 GPa.
[0028] In some embodiments of the present application, the Young's modulus E of the glass-ceramics is 98.8 GPa, 99 GPa, 99.45 GPa or 110 GPa.
[0029] In some embodiments of the present application, the components of the microcrystalline glass include, by mass percentage of oxides: SiO2: 55% to 75%, Al2O3: 5% to 15%, P2O5: 1% to 6%, ZrO2: 2% to 10%, Na2O: 0 to 15%, K2O: 0 to 7%, Sb2O3: 0 to 1%, SnO2: 0 to 1%, CaO: 0 to 3%, Li2O: 5% to 25%, B2O3: 0 to 5%, Y2O3: 0 to 5%, MgO: 0 to 5%. In the present application, appropriate components can be selected and the content range of each oxide component can be controlled as needed to obtain microcrystalline glass that meets specific crystal phase structure, optical properties and mechanical strength properties, and then obtain ultra-thin microcrystalline glass with high bending performance.
[0030] In some embodiments of the present application, the mass percentage of SiO2 in the glass-ceramics is 55.3%, 70.55%, 70.7% or 70.8%; and / or,
[0031] The mass percentage of Al2O3 in the glass-ceramics is 7.11%, 7.4%, 7.6% or 10.57%; and / or,
[0032] The mass percentage of P2O5 in the glass-ceramics is 2.27%, 2.34%, 2.53% or 4.5%; and / or,
[0033] The mass percentage of ZrO2 in the glass-ceramics is 3.8%, 5.32%, 5.65% or 6.39%; and / or,
[0034] The mass percentage of Na2O in the glass-ceramics is 0.88%, 2.06%, 2.5% or 3.36%; and / or,
[0035] The mass percentage of K2O in the glass-ceramics is 0% or 1.76%; and / or,
[0036] The mass percentage of Sb2O3 in the glass-ceramics is 0% or 0.3%; and / or,
[0037] The mass percentage of SnO2 in the glass-ceramics is 0%, 0.25% or 0.35%; and / or,
[0038] The mass percentage of CaO in the glass-ceramics is 0% or 0.88%; and / or,
[0039] The mass percentage of Li2O in the glass-ceramics is 10.78%, 11.17%, 11.2% or 15.21%; and / or,
[0040] The mass percentage of B2O3 in the glass-ceramics is 0.2%, 0.35%, 0.6% or 2.05%; and / or,
[0041] The mass percentage of Y2O3 in the glass-ceramics is 0% or 2.78%; and / or
[0042] The mass percentage of MgO in the glass-ceramics is 0% or 0.49%.
[0043] In some embodiments of the present application, the main crystalline phase of the microcrystalline glass includes at least one of lithium phosphate, spodumene, lithium monosilicate, lithium disilicate, petalite, nepheline and β-quartz solid solution. Preferably, the main crystalline phase of the microcrystalline glass includes at least one of lithium monosilicate, lithium disilicate and petalite; and / or,
[0044] Among all the crystal phases of the glass-ceramics, the mass proportion of the main crystal phase is ≥50%; and / or,
[0045] The crystallinity of the glass-ceramics is ≥10%, preferably ≥50%; and / or,
[0046] The average grain size of the microcrystalline glass is 6nm to 100nm, preferably 10nm to 50nm, and more preferably 15nm to 30nm. In the present application, microcrystalline glass that meets specific crystal phase structure, optical properties, mechanical strength properties, etc. can be used as needed to prepare ultra-thin microcrystalline glass with high bending performance.
[0047] In some embodiments of the present application, the mass percentage of the main crystalline phase of the glass-ceramics is 50%, 93% or 95%; and / or,
[0048] The crystallinity of the glass-ceramic is 50%, 67%, 88% or 90%; and / or,
[0049] The average grain size of the glass-ceramics is 15 nm, 20 nm or 25 nm.
[0050] In some embodiments of the present application, the microcrystalline glass is transparent in the visible light wavelength range, preferably, for 550nm wavelength light, the transmittance of the microcrystalline glass is ≥85%, preferably, the transmittance is ≥90%. Microcrystalline glass that meets this transmittance can ensure good display effect and transparency effect, and is suitable for use in electronic device display screens that require display effect.
[0051] In some embodiments of the present application, for light with a wavelength of 550 nm, the transmittance of the microcrystalline glass is 90.60%, 90.70%, 90.90% or 91.00%.
[0052] In some embodiments of the present application, the density of the microcrystalline glass is 2.4 g / cm 3 ~2.7g / cm 3, preferably 2.5 g / cm 3 ~2.6g / cm 3 and / or,
[0053] The refractive index of the glass-ceramics is ≤1.6, preferably, the refractive index is 1.5 to 1.6; and / or
[0054] The Poisson's ratio of the microcrystalline glass is 0.2 to 0.3. The density and / or refractive index and / or Poisson's ratio are within the above range, indicating that the microcrystalline glass has a high intrinsic strength / inherent strength, which is conducive to achieving excellent mechanical strength and excellent damage resistance.
[0055] In some embodiments of the present application, the density of the microcrystalline glass is 2.48 g / cm 3 , 2.5g / cm 3 , 2.51g / cm 3 or 2.59 g / cm 3 and / or,
[0056] The refractive index of the glass-ceramic is 1.54 or 1.57; and / or,
[0057] The Poisson's ratio of the glass-ceramics is 0.2, 0.21, 0.22 or 0.23.
[0058] In some embodiments of the present application, the components of the microcrystalline glass include, in terms of mass percentage of oxides: SiO2: 55% to 72%, Al2O3: 6% to 12%, P2O5: 1.5% to 5%, ZrO2: 2.5% to 7.5%, Na2O: 0 to 4%, K2O: 0 to 3%, Sb2O3: 0 to 1%, SnO2: 0 to 1%, CaO: 0 to 3%, Li2O: 10% to 17%, B2O3: 0 to 3%, Y2O3: 0 to 5%, and MgO: 0 to 3%.
[0059] In some embodiments of the present application, the surface of the microcrystalline glass has a compressive stress layer and the interior has a tensile stress layer. By chemically strengthening the ultra-thin microcrystalline glass with a surface roughness as small as possible and a specific edge shape chamfer structure, the bending performance of the ultra-thin microcrystalline glass can be improved to a higher range, thereby significantly improving the bending performance and bending life of the ultra-thin microcrystalline glass.
[0060] In some embodiments of the present application, the static limit bending radius R of the microcrystalline glass is 极限 Satisfy R 极限 ≤0.1492e Et / 1.40622 +0.0038E, wherein e is a natural base, E is the Young's modulus of the glass-ceramics, in GPa, and t is the thickness of the glass-ceramics, in mm; and / or,
[0061] The glass-ceramic is subjected to a bending life test. The glass-ceramic is subjected to a dynamic bending number of ≥50,000 times at a bending radius of 1.346Et / 2, wherein E is the Young's modulus of the glass-ceramic, in GPa, and t is the thickness of the glass-ceramic, in mm. The smaller the measured static limit bending radius Rlimit and / or the greater the dynamic bending number, the better the bending performance of the glass-ceramic.
[0062] In some embodiments of the present application, the static limit bending radius R of the microcrystalline glass is 极限 (mm)≤R2.0, preferably ≤R1.5; and / or,
[0063] A bending life test is performed on the microcrystalline glass. When the microcrystalline glass is bent at a bending radius of R2.0, the number of dynamic bending times is ≥50,000 times.
[0064] In some embodiments of the present application, the static limit bending radius R of the microcrystalline glass is 极限 R1.3 or R1.5; and / or, the dynamic bending times of the glass-ceramic are ≥50,000 times when the bending radius is R2.0, R1.9 or R1.7.
[0065] In some embodiments of the present application, at least one major surface of the glass-ceramic includes a coating layer or a stacked layer of an organic or inorganic material.
[0066] In a second aspect, a method for preparing the aforementioned microcrystalline glass is provided, the method comprising the following steps:
[0067] The microcrystalline glass substrate is thinned to obtain a primary microcrystalline glass product; preferably, the microcrystalline glass substrate is etched and thinned by an etching solution, and the etching solution preferably includes one or more of hydrofluoric acid, nitric acid, sulfuric acid, and hydrochloric acid. More preferably, the etching solution comprises 1% to 10% hydrofluoric acid, 5% to 10% nitric acid, 0% to 5% sulfuric acid, 0% to 5% hydrochloric acid and water by mass percentage, and the etching temperature is preferably 20 to 50° C., and the etching time is preferably 5 min to 200 min;
[0068] The obtained glass-ceramics primary product is edge-processed so that the side surface of the glass-ceramics forms a chamfer with an arc-shaped edge, and a glass-ceramics with a chamfered structure is obtained. The glass-ceramics with a chamfer meets the following requirements: the surface roughness Ra of the main surface is ≤150nm, a coordinate system is established in a cross section perpendicular to the side surface along the thickness direction, the symmetry axis of the two main surfaces of the glass-ceramics is taken as the x-axis, and a straight line passing through the chamfer starting point on the main surface and perpendicular to the x-axis is taken as the y-axis, and the edge curve of the chamfer meets the following relationship:
[0069]
[0070] Wherein, k satisfies 0.36≤k≤3.52, preferably, 0.36≤k≤3, and more preferably, 0.36≤k≤2.5, and t is the thickness of the microcrystalline glass, in mm.
[0071] In some embodiments of the present application, the thickness of the microcrystalline glass substrate is ≤0.6 mm, the difference between the maximum thickness and the minimum thickness of the microcrystalline glass substrate TTV is ≤3 μm, and the Young's modulus of the microcrystalline glass substrate is preferably 80 GPa to 130 GPa;
[0072] And / or, the thickness of the primary microcrystalline glass product is ≤ 0.2 mm, preferably 0.02 mm to 0.2 mm, more preferably 0.02 mm to 0.1 mm, and more preferably 0.02 mm to 0.05 mm. In the present application, the smaller the thickness of the microcrystalline glass substrate and / or the smaller the difference TTV between the maximum thickness and the minimum thickness, the more uniform the thickness of the primary microcrystalline glass product after the thinning process can be ensured, and the risk of fragmentation during the thinning process can be reduced, thereby improving the thinning efficiency.
[0073] In some embodiments of the present application, the method further includes, after the edge treatment, chemically strengthening the obtained microcrystalline glass with a chamfered structure to form a compressive stress layer on the surface of the microcrystalline glass. Preferably, the salt bath composition for chemical strengthening treatment includes 0.01-0.30wt% lithium salt (one of lithium nitrate and lithium sulfate) and 1-99wt% sodium salt (one of sodium nitrate, sodium sulfate and sodium carbonate) and 1-99wt% potassium salt (one of potassium nitrate, potassium sulfate and potassium carbonate). The preferred chemical strengthening treatment salt bath temperature is 370℃~550℃, and the preferred chemical strengthening treatment time is 5min~240min. In the present application, the chemical strengthening treatment forms an ion exchange layer on the surface of the microcrystalline glass, and a certain compressive stress is generated on the surface to form a compressive stress layer. When the microcrystalline glass is bent, the compressive stress generated on the surface will first offset the force on the surface, that is, the formation of the surface compressive stress layer is conducive to improving the bending strength of the microcrystalline glass. At the same time, the compressive stress layer formed by the chemical strengthening treatment can effectively eliminate or inhibit the further expansion of microcracks, thereby helping to improve the ability of microcrystalline glass to resist external forces and enhance the bending performance of microcrystalline glass.
[0074] In some embodiments of the present application, the method further includes, after the chemical strengthening treatment, performing surface strengthening treatment on the obtained microcrystalline glass having a compressive stress layer on the surface. Preferably, the surface strengthening treatment is performed by chemical polishing. For example, the microcrystalline glass having a compressive stress layer is preferably placed in an etching solution for surface strengthening treatment. Preferably, the etching solution contains one or more of hydrofluoric acid, nitric acid, hydrochloric acid, and sulfuric acid. Preferably, by mass percentage, the composition of the etching solution includes 0.1% to 2% hydrofluoric acid, 0.5 to 2% nitric acid, 0% to 1% hydrochloric acid, 0 to 1% sulfuric acid and water. Preferably, the etching time is 60s to 1200s, and the etching temperature is 20°C to 50°C. In the present application, chemical polishing of the surface of the microcrystalline glass having a compressive stress layer can improve the uniformity of the surface of the microcrystalline glass and passivate the microcracks on the surface of the microcrystalline glass, thereby facilitating the improvement of the ability of the microcrystalline glass to resist external forces and the improvement of the bending performance of the microcrystalline glass.
[0075] In some embodiments of the present application, the edge treatment includes chemically etching the initial microcrystalline glass product using an etching solution. Preferably, the etching solution includes one or more of hydrofluoric acid, nitric acid, sulfuric acid, and hydrochloric acid. More preferably, the etching solution is composed of 1% to 10% hydrofluoric acid, 1% to 10% nitric acid, 0% to 5% sulfuric acid and water, and preferably, during the etching treatment, the etching temperature is 20°C to 50°C, and the etching time is 60s to 3600s.
[0076] In some embodiments of the present application, before edge treatment, the step of coating the primary glass-ceramics product is also included to form an acid-resistant coating on the main surface of the primary glass-ceramics product;
[0077] After the edge treatment, the method also includes the step of demolding the microcrystalline glass with a chamfered structure. Preferably, a demolding agent is used to demold the microcrystalline glass. Preferably, the demolding agent includes one or more of sodium hydroxide, sodium bicarbonate, and sodium carbonate. Preferably, the composition of the demolding agent includes 1-20% sodium hydroxide, 0%-20% sodium bicarbonate, 0%-20% sodium carbonate and water in mass percentage. Preferably, the demolding treatment temperature is 50°C to 90°C, and the demolding treatment time is 1min to 120min.
[0078] In some embodiments of the present application, the step of coating the microcrystalline glass after surface strength treatment may also be included to form a coating layer or a stacked layer of organic or inorganic material on at least one main surface of the microcrystalline glass, which is conducive to better application of the microcrystalline glass.
[0079] In a third aspect, a cover glass is provided, wherein the cover glass comprises the microcrystalline glass of any embodiment of the first aspect or the microcrystalline glass made by the method of any embodiment of the second aspect. The cover glass can be a display cover, a sensor module cover or a thin film battery cover of an electronic device.
[0080] In a fourth aspect, an electronic device is provided, comprising the microcrystalline glass according to any embodiment of the first aspect or the microcrystalline glass produced by the method of any embodiment of the second aspect.
[0081] In some embodiments of the present application, the electronic device includes a shell assembled on the outside of the electronic device, and the shell includes the microcrystalline glass according to any embodiment of the first aspect or the microcrystalline glass made by the method of any embodiment of the second aspect.
[0082] In some embodiments of the present application, the housing includes a display cover assembled on the front side of the electronic device, and the display cover includes the microcrystalline glass of any embodiment of the first aspect or the microcrystalline glass made by the method of any embodiment of the second aspect.
[0083] In some embodiments of the present application, the electronic device includes a foldable electronic device, a display, a sensor, a semiconductor package or a thin film battery, preferably the sensor includes a fragile sensor, a fingerprint sensor or an image sensor, and preferably the microcrystalline glass is applied to a substrate or a cover of the electronic device.
[0084] In some embodiments, the housing may be partially or entirely made of glass-ceramics. At least one major surface of the glass-ceramics may include a coating layer or a laminated layer of an organic or inorganic material.
[0085] In a fifth aspect, a glass device is provided, the glass device comprising the microcrystalline glass according to any embodiment of the first aspect or the microcrystalline glass produced by the method of any embodiment of the second aspect.
[0086] One or more of the above technical solutions provided by the present application have the following advantages compared with the prior art:
[0087] The present application makes the surface roughness of the main surface of the ultra-thin microcrystalline glass meet a specific range. At the same time, during edge processing, the ultra-thin microcrystalline glass is formed into a chamfered structure with a specific edge shape, which is beneficial to reduce the risk of breakage due to edge stress concentration during the bending process, and is beneficial to obtaining ultra-thin microcrystalline glass with better bending performance after chemical strengthening treatment, so that the microcrystalline glass has better bending performance and a higher bending life. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] The accompanying drawings herein are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present application, and together with the specification are used to explain the principles of the present application. It should be understood that the following drawings only illustrate certain embodiments of the present application and therefore should not be considered to limit the scope of the present application.
[0089] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0090] Figure 1 A schematic diagram of the cross-sectional structure of the glass-ceramics of an embodiment of the present application;
[0091] Figure 2 A schematic diagram of a process for preparing glass-ceramics according to an embodiment of the present application;
[0092] Figure 3 It is a fitting diagram of the chamfered edges of the glass-ceramics of Examples 1 and 2 and Comparative Examples 8 and 9 of the present application;
[0093] Figure 4 This is a 40-fold magnified morphology image of the chamfer of the microcrystalline glass of Example 1 of the present application;
[0094] Figure 5 This is a surface morphology image of the glass-ceramics of Example 2 of the present application magnified 20 times;
[0095] Figure 6 This is a schematic diagram of the front structure of the electronic device mentioned in the embodiment of the present application;
[0096] Figure 7 A schematic diagram of the rear structure of the electronic device mentioned in the embodiment of the present application;
[0097] Reference numerals: A-first main surface, B-second main surface, C-side surface, A'-chamfering starting point, B'-chamfering end point;
[0098] 1-housing; 11-display cover; 12-back cover; 13-camera protection cover; 2-camera assembly; 3-first chamfer; 4-second chamfer. DETAILED DESCRIPTION
[0099] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0100] The endpoints and any values of the ranges disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all refer to including or not including (or may have or may not have). "And / or" as referred to herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0101] Explanation of terms and test methods:
[0102] In the present application, glass-ceramics is a type of solid composite material that is prepared by targeted controlled heat treatment of substrate glass and contains both a glass phase and a crystal phase (also called a microcrystalline phase or a crystal phase). Glass-ceramics are also called glass ceramics or crystallized glass.
[0103] In the present application, the edge curve of the chamfer refers to: a coordinate system is established in the cross section perpendicular to the side surface along the thickness direction, with the symmetry axis of the two main surfaces of the microcrystalline glass as the x-axis, and a straight line passing through the chamfer starting point on the main surface and perpendicular to the x-axis as the y-axis, and the arc curve between the chamfer starting point A' and the chamfer end point B' on the main surface is recorded as the edge curve of the chamfer, which can be seen in Figure 3 .
[0104] In the present application, the bending performance of glass-ceramics refers to the ability of the glass-ceramics to resist bending force without breaking when subjected to bending force.
[0105] In the present application, substrate glass (or also referred to as base glass) refers to glass that has not been subjected to nucleation treatment, crystallization treatment, and strengthening treatment.
[0106] In the present application, nucleation treatment refers to growing crystal nuclei in the substrate glass by heat treatment; crystallization treatment refers to precipitating target crystals or crystalline phases in the substrate glass by heat treatment.
[0107] In the present application, the visible light wavelength range refers to 360nm to 740nm.
[0108] In the present application, the main crystalline phase (or also referred to as the main crystalline phase) refers to a crystalline phase having a higher mass content (or also referred to as weight percentage, mass percentage) than other crystalline phases present in the microcrystalline glass.
[0109] In the present application, the main surface refers to the surface with the largest surface area, such as the upper surface or lower surface of a horizontally placed microcrystalline glass sheet.
[0110] In the present application, crystallinity refers to the percentage of the total mass of the crystalline phase in the microcrystalline glass to the mass of the microcrystalline glass, or is also called the total content of the crystalline phase in the microcrystalline glass.
[0111] In the present application, when light of a certain wavelength is irradiated onto the main surface of the microcrystalline glass, the light will be reflected, absorbed and transmitted, and the ratio of the intensity of the transmitted part to the intensity of the incident light is the transmittance.
[0112] In this application, the refractive index refers to the ratio of the propagation speed of light in a vacuum to the propagation speed of light in the medium.
[0113] In this application, the thickness is measured by a digital micrometer Mitutoyo 406-250-30. It should be understood that in the thickness direction of the glass-ceramic sample, the degree of ion exchange changes gradually from the surface to the center, and the overall Na-K and / or Li-Na exchange increment (mass) generally does not exceed 1.5% of the total mass of the sample. Therefore, the expansion effect in the thickness direction is extremely slight, and it can be approximately considered that the thickness has basically not changed. That is, before and after chemical strengthening, the thickness of the glass-ceramic changes very little, which can be basically ignored, and the thickness of the glass-ceramic is basically the same as the thickness of the chemically strengthened glass-ceramic obtained therefrom.
[0114] In this application, the size specifications of the microcrystalline glass sheet are tested using a two-dimensional measuring machine (the instrument model is Miyu MY-YXCL-4030).
[0115] In this application, Young's modulus is used to characterize the ability of glass to resist elastic deformation due to external force. This application uses UMS-100 ultrasonic material characterization system to test the Young's modulus of microcrystalline glass by sound waves.
[0116] In this application, the crystal phase, crystallinity and average grain size of the glass-ceramics are confirmed by XRD testing. Specifically:
[0117] (1) XRD test: The microcrystalline glass of the present application was crushed and ground into a sample with a particle size of less than 75 μm, and the ground sample was tested using an X-ray diffractometer to obtain an XRD diffraction peak curve and XRD diffraction data. The X-ray diffractometer used in the present application is Shimadzu XRD-6100, the target material is copper, 2θ=10°-50°, the scanning speed is 0.2° / min, the operating voltage is 40 kV, and the operating current is 30 mA.
[0118] (2) Determination of crystalline phase: XRD diffraction data were analyzed using Jade software (JADE Standard 8.6) to determine the crystalline phase in the sample.
[0119] (3) Determination of crystallinity (also known as total crystalline content): The XRD test results (RAW format) are imported into the Jade software for fitting and calculation to determine the crystallinity of the sample. Specifically, the ratio of the fitted crystalline phase peak area to the fitted total peak area is recorded as the crystallinity of the sample.
[0120] (4) Determination of average grain size (or also called average crystal size): The average grain size of the sample can be calculated using the result data obtained from the XRD test according to the Scherrer formula D = Kλ / (βcosθ). Wherein, λ is the wavelength of the X-ray, λ = 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW format file output by the XRD instrument is curve fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and Peak FWHM value corresponding to each diffraction peak in the fitting report, the Peak FWHM value is converted into radians: β = (FWHM / 180×3.14), and the grain size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain the average grain size in the sample.
[0121] In this application, with reference to the national standard "GB / T 7962.12-2010 Test Method for Colorless Optical Glass Part 12: Spectral Transmittance", a haze meter is used to test the transmittance and b value of the microcrystalline glass of this application. Specifically, the haze meter is used to test the transmittance of 5 microcrystalline glass pieces of the same batch to light of different wavelengths. The average value of the transmittance of the 5 microcrystalline glass pieces measured at a wavelength of 550nm is taken as the transmittance result of the microcrystalline glass at a wavelength of 550nm. The haze meter used in the test of this application is a Japanese Konica Minolta spectrophotometer CM-3600A, the light receiving optical system is transmission, the light splitting method is a plane refractive grating, the wavelength range is 360nm-740nm, the wavelength spacing is 10nm, the illumination light source is a pulse xenon lamp × 4, the ambient temperature of the instrument is 24℃, and the air humidity is 40%.
[0122] Density test: In this application, the electronic density balance SD-200L of Japan ALFA MIRAGE is used to test the density of microcrystalline glass.
[0123] Refractive index test: In this application, the refractive index of microcrystalline glass was tested using Abbe refractometer WYA-2WAJ produced by Shanghai Lichen Bangxi Instrument Technology Co., Ltd., China.
[0124] Surface roughness test: In this application, the ER-230 white light interferometer of UCO was used to measure the surface roughness of the microcrystalline glass.
[0125] Limit bending radius R 极限Test: In this application, Huitong WH-1480 two-point bending tester was used to measure the ultimate bending radius of microcrystalline glass.
[0126] Bending durability test: In this application, Huitong WH-1711 bending durability tester is used to measure the bending life of microcrystalline glass.
[0127] Determination of the relationship / function satisfied by the edge morphology and the chamfer edge curve: Use the MY-YXCL-4030 two-dimensional measuring instrument to observe the edge morphology of the chamfer. In the cross section perpendicular to the side surface along the thickness direction, take the symmetry axis of the two main surfaces of the microcrystalline glass as the x-axis, and take the straight line passing through the chamfer starting point on the main surface and perpendicular to the x-axis as the y-axis to establish a coordinate system, measure the chamfer width a and the chamfer height b, and obtain the coordinates of the chamfer starting point A' and the chamfer end point B'. Then introduce the elliptic function equation to fit, and you can get the relationship / function satisfied by the edge curve of the chamfer.
[0128] Microcrystalline UTG has excellent hardness, scratch resistance, impact resistance, deformation resistance, drop resistance, and anti-scattering properties, and has broad application prospects in folding screen cover materials. However, since the microcrystalline glass on the market generally has high brittleness and Young's modulus, the microcrystalline UTG obtained by thinning it is very easy to have insufficient bending performance.
[0129] Without being bound by any theory, the inventors have found that, similar to ultra-thin glass (UTG), the edge chamfer structure of ultra-thin microcrystalline glass (microcrystalline UTG) also has a significant effect on its bending performance. The characteristics of the edge chamfer structure are very important for improving the bending performance and bending life of ultra-thin microcrystalline glass products. However, unlike ultra-thin glass (UTG), the bending performance and bending life of microcrystalline UTG cannot be improved to a higher range only by controlling the ratio of chamfer width a and chamfer height b, the ratio of chamfer width a and microcrystalline glass thickness t, and performing chemical strengthening treatment. The resulting microcrystalline UTG still has the problem of insufficient bending performance.
[0130] Furthermore, the inventors found that when preparing ultra-thin glass-ceramics, by making the surface roughness of the ultra-thin glass-ceramics as small as possible,
[0131] At the same time, during edge processing, the ultra-thin microcrystalline glass is formed into a chamfered structure with a specific edge shape, which is conducive to obtaining ultra-thin microcrystalline glass with better bending performance after chemical strengthening treatment.
[0132] In order to improve the problem of poor bending performance of ultra-thin microcrystalline glass (microcrystalline UTG), the present application provides a microcrystalline glass and a cover glass, electronic device and glass device containing the microcrystalline glass. The microcrystalline glass is an ultra-thin microcrystalline glass, the roughness of its main surface meets a specific range, and it has an arc chamfer, and the edge curve of the chamfer meets a specific relationship / function, which is beneficial to reduce the risk of breakage due to edge stress concentration during bending, so that the microcrystalline glass has better bending performance and a higher bending life.
[0133] As mentioned above, in some embodiments of the present application, a microcrystalline glass is provided. Figure 1 Schematic diagram of the cross-sectional structure of the glass-ceramics of the present application embodiment. Figure 1 As shown, the microcrystalline glass includes a first main surface, a second main surface, and at least one side surface connecting the first main surface and the second main surface;
[0134] The surface roughness Ra of the first main surface and the second main surface satisfies: Ra≤150nm, preferably, Ra≤145nm, more preferably, Ra≤140nm;
[0135] In the microcrystalline glass, at least one of the side surfaces has at least one chamfer, and the edge of the chamfer is arc-shaped. A coordinate system is established in a cross section perpendicular to the side surface along the thickness direction, with the symmetry axis of the two main surfaces of the microcrystalline glass as the x-axis, and a straight line passing through the starting point of the chamfer on the main surface and perpendicular to the x-axis as the y-axis. The coordinate system can be found in Figure 3 , the chamfered edge curve satisfies the following relationship:
[0136]
[0137] Wherein, k satisfies 0.36≤k≤3.52, preferably, 0.36≤k≤3, and more preferably, 0.36≤k≤2.5, and t is the thickness of the microcrystalline glass, in mm.
[0138] The present application reduces the risk of breakage due to edge stress concentration during bending by making the surface roughness of the microcrystalline glass meet a specific range and making the edge of the microcrystalline glass form an arc chamfer that meets a specific relationship, so that the microcrystalline glass has better bending performance and a longer bending life. In the present application, the edge chamfer structure of the side surface of the microcrystalline glass can be formed by, but not limited to, chemical etching.
[0139] In some embodiments, the surface roughness Ra of the main surface (such as the first main surface and the second main surface) of the microcrystalline glass can be 55nm to 140nm. In some embodiments, the surface roughness Ra can be 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 55nm or 96nm, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass with the desired performance of the present application can be obtained.
[0140] In some embodiments, the edge curve of the chamfer satisfies the relationship in which the value of k is 0.36 to 2.08. In some embodiments, the edge curve of the chamfer satisfies the relationship in which the value of k can be 0.36, 1, 1.5, 2, 2.5, 3, 3.5, 3.52, 1.12, 1.69 or 2.08, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass with the required performance of the present application can be obtained.
[0141] In some embodiments of the present application, the glass-ceramics is in the form of a plate or sheet, and preferably the thickness t of the glass-ceramics is 0.02 mm to 0.2 mm, preferably 0.02 mm to 0.1 mm, and more preferably 0.02 mm to 0.05 mm. In some embodiments, the thickness t of the glass-ceramics of the present application can be 0.02 mm, 0.025 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.10 mm, 0.11 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.17 mm, 0.18 mm, 0.19 mm or 0.2 mm, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass with the performance required by the present application can be obtained. For foldable electronic devices, the smaller the thickness of the cover glass, the easier it is to achieve the bending effect, and the smaller the thickness, the lighter the weight, and the easier it is to obtain excellent optical effects. The present application can make the microcrystalline glass product as thin as possible while ensuring strength to meet the requirements of foldable electronic devices.
[0142] In some embodiments of the present application, in the glass-ceramic, at least one side surface has a first chamfer facing the first main surface and a second chamfer facing the second main surface, and the first chamfer and the second chamfer are substantially symmetrical on both sides of the glass-ceramic. Here, "substantially symmetrical" means that the edge chamfer structure of the glass-ceramic is substantially symmetrical with the symmetry axis of the two main surfaces of the glass-ceramic as the symmetry axis.
[0143] In some embodiments of the present application, at least two side surfaces in the length direction of the microcrystalline glass have chamfers, and more preferably, four side surfaces of the microcrystalline glass have chamfers, and preferably the chamfers include a substantially symmetrical first chamfer facing the first main surface and a second chamfer facing the second main surface. Such a chamfer structure is conducive to reducing the risk of breakage due to edge stress concentration during bending.
[0144] In the present application, the microcrystalline glass includes two main surfaces and four side surfaces, the two main surfaces are respectively a first main surface and a second main surface, and the four side surfaces are respectively: two side surfaces I connecting the first main surface and the second main surface along the length direction of the microcrystalline glass, and two side surfaces II connecting the first main surface and the second main surface along the width direction of the microcrystalline glass. Exemplary:
[0145] In some embodiments, at least one side surface I or side surface II has at least one arc chamfer, preferably two arc chamfers, namely, a first chamfer toward the first main surface and a second chamfer toward the second main surface, and the two arc chamfers are substantially symmetrical.
[0146] In some embodiments, both side surfaces I or both side surfaces II have arc chamfers, preferably both side surfaces I or both side surfaces II have two arc chamfers, i.e., a first chamfer facing the first main surface and a second chamfer facing the second main surface, preferably, the two arc chamfers on each side surface are substantially symmetrical, more preferably, the arc chamfers on the two side surfaces I are substantially symmetrical or the arc chamfers on the two side surfaces II are substantially symmetrical. Figure 3 It is understandable that there may be two arc chamfers on one side surface I or side surface II, and one arc chamfer on the other side surface I or side surface II.
[0147] In some embodiments, both side surfaces I and both side surfaces II have arc chamfers, and preferably each side surface has two arc chamfers, i.e., a first chamfer facing the first main surface and a second chamfer facing the second main surface. Preferably, the two arc chamfers on each side surface are basically symmetrical, and more preferably, the arc chamfers on the two side surfaces I are basically symmetrical, and the arc chamfers on the two side surfaces II are basically symmetrical.
[0148] In some embodiments of the present application, the chamfer has a chamfer width a and a chamfer height b, and the chamfer width a and chamfer height b of the chamfer satisfy: 1≤a / b≤20, preferably, 1≤a / b≤10, and more preferably, 1.2≤a / b≤6. The width direction of the chamfer is the same as the extension direction of the main surface of the microcrystalline glass to the side surface, and the height direction of the chamfer is the same as the thickness direction of the microcrystalline glass. In the present application, by making the ratio of the chamfer width a and the chamfer height b of the chamfer satisfy a specific range, it is beneficial to form a specific chamfer edge shape, thereby reducing the risk of breakage caused by edge stress concentration during bending, so that the microcrystalline glass has better bending performance.
[0149] In some embodiments, the ratio a / b of the chamfer width a and the chamfer height b of the chamfer can be 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 1.2, 3, 4.7 or 5.4, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass with the performance required by the present application can be obtained.
[0150] In some embodiments of the present application, the chamfer width a of the chamfer and the thickness t of the glass-ceramics satisfy: 0.6≤a / t≤1.5, preferably: 0.6≤a / t≤1.4, and more preferably, 0.6≤a / t≤1.2. In the present application, by making the ratio of the chamfer width a of the chamfer and the thickness t of the glass-ceramics meet a specific range, it is beneficial to form a specific chamfer edge shape, which is beneficial to reduce the risk of breakage caused by edge stress concentration during the bending process, so that the glass-ceramics has better bending performance.
[0151] In some embodiments, the ratio a / t of the chamfer width a to the thickness t of the glass-ceramics may be 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4 or 1.5, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the desired performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass-ceramics with the desired performance of the present application can be obtained.
[0152] In some embodiments of the present application, the Young's modulus E of the microcrystalline glass is 80GPa to 130GPa, preferably 90GPa to 120GPa, more preferably 95GPa to 115GPa, and more preferably 98.8GPa to 110GPa. In the present application, an excessively high Young's modulus makes the microcrystalline glass more susceptible to brittle fracture when bent, and reduces the shaping ability of the microcrystalline glass, which is not conducive to obtaining excellent bending performance; but an excessively small Young's modulus is not conducive to the deformation resistance and impact resistance of the microcrystalline glass. Therefore, in order to take into account the bending performance, deformation resistance and impact resistance of the microcrystalline glass, the present application makes the Young's modulus E of the microcrystalline glass meet 80GPa to 130GPa. It should be understood that the Young's modulus of the microcrystalline glass is generally unrelated to the thickness, so after thinning, the Young's modulus of the microcrystalline glass does not change or substantially does not change.
[0153] In some embodiments, the Young's modulus E of the glass-ceramics may be 80 GPa, 85 GPa, 90 GPa, 95 GPa, 100 GPa, 105 GPa, 98.8 GPa, 99 GPa, 99.45 GPa, 110 GPa, 115 GPa, 120 GPa, 125 GPa or 130 GPa, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the desired performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass-ceramics with the desired performance of the present application can be obtained.
[0154] In the present application, the microcrystalline glass can be obtained by heat treating a substrate glass, and the composition of the substrate glass is the same or substantially the same as that of the microcrystalline glass in terms of molar percentage or mass percentage of oxides.
[0155] In some embodiments of the present application, the components of the microcrystalline glass include, by mass percentage of oxides: SiO2: 55% to 75%, Al2O3: 5% to 15%, P2O5: 1% to 6%, ZrO2: 2% to 10%, Na2O: 0 to 15%, K2O: 0 to 7%, Sb2O3: 0 to 1%, SnO2: 0 to 1%, CaO: 0 to 3%, Li2O: 5% to 25%, B2O3: 0 to 5%, Y2O3: 0 to 5%, MgO: 0 to 5%. In the present application, appropriate components can be selected and the content range of each oxide component can be controlled as needed to obtain microcrystalline glass that meets specific crystal phase structure, optical properties and mechanical strength properties, and then obtain ultra-thin microcrystalline glass with high bending performance.
[0156] In some embodiments of the present application, the components of the microcrystalline glass include, in terms of mass percentage of oxides: SiO2: 55% to 72%, Al2O3: 6% to 12%, P2O5: 1.5% to 5%, ZrO2: 2.5% to 7.5%, Na2O: 0 to 4%, K2O: 0 to 3%, Sb2O3: 0 to 1%, SnO2: 0 to 1%, CaO: 0 to 3%, Li2O: 10% to 17%, B2O3: 0 to 3%, Y2O3: 0 to 5%, and MgO: 0 to 3%.
[0157] It can be understood that the composition of the substrate glass or the composition of the microcrystalline glass or the composition at the center of the chemically strengthened microcrystalline glass obtained by chemically strengthening the microcrystalline glass can be transformed by conversion. For example, the above-mentioned measurement method of mass percentage of oxide can be converted into molar percentage of oxide.
[0158] In some embodiments of the present application, the main crystalline phase of the microcrystalline glass includes at least one of lithium phosphate, spodumene, lithium monosilicate, lithium disilicate, petalite, nepheline and β-quartz solid solution. Preferably, the main crystalline phase of the microcrystalline glass includes at least one of lithium monosilicate, lithium disilicate and petalite. In the present application, microcrystalline glass that meets specific crystal phase structure, optical properties and mechanical strength properties can be used as needed to prepare ultra-thin microcrystalline glass with high bending performance.
[0159] In the present application, "the main crystalline phase includes at least one of lithium phosphate, spodumene, lithium monosilicate, lithium disilicate, petalite, nepheline and β-quartz solid solution" or other similar expressions means that the mass of at least one of lithium phosphate, spodumene, lithium monosilicate, lithium disilicate, petalite, nepheline and β-quartz solid solution accounts for more than 50% (mass % or wt %) of all crystalline phases of the microcrystalline glass according to the embodiment of the present application. The mass fraction of the main crystalline phase is equal to the mass of the main crystalline phase divided by the sum of the masses of all crystalline phases of the microcrystalline glass. Increasing the mass fraction of the main crystalline phase can effectively reduce the scattering phenomenon of different crystalline phases, improve the optical transmittance of the microcrystalline glass, and reduce the haze of the microcrystalline glass after etching, thereby helping to improve the optical properties of the microcrystalline glass. In some embodiments, among all the crystalline phases of the glass-ceramics, the mass proportion of the main crystalline phase can be 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics with the required performance of the present application can be obtained.
[0160] In some embodiments of the present application, the crystallinity of the glass-ceramics is ≥10%, preferably, the crystallinity is ≥50%, preferably, the crystallinity is not less than 65%, preferably, the crystallinity is not less than 70%, preferably, the crystallinity of the glass-ceramics or the chemically strengthened glass-ceramics obtained by chemical strengthening treatment of the glass-ceramics is 70% to 90%. In the present application, the crystallinity is equal to the mass of all crystalline phases divided by the mass of the glass-ceramics. The high crystallinity of the glass-ceramics is conducive to obtaining high mechanical strength and high damage resistance, thereby helping to improve the impact resistance of the ultra-thin glass-ceramics obtained.
[0161] In some embodiments, the crystallinity of the glass-ceramics may be 50%, 55%, 60%, 65%, 70%, 72%, 74%, 76%, 78%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90% or 67%, or may be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the desired performance of the present application can be obtained. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the glass-ceramics with the desired performance of the present application can be obtained.
[0162] In some embodiments of the present application, in the glass-ceramics, the average grain size does not exceed 100nm, preferably, the average grain size is 6nm to 100nm; preferably 10nm to 50nm, more preferably 15nm to 30nm. The appropriate average grain size is conducive to the glass-ceramics to obtain excellent optical properties. If the average grain size is too high, the glass-ceramics is prone to devitrification and is also prone to affect the surface roughness of the glass-ceramics after etching. In some embodiments, the average grain size of the glass-ceramics can be 100nm, 50nm, 40nm, 35nm, 30nm, 25nm, 20nm, 15nm, 10nm or 6nm, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the desired performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics with the desired performance of the present application can be obtained.
[0163] SiO2 is a glass network-forming oxide and an indispensable component of the glass network structure. At the same time, SiO2 is also an important component of crystalline phases such as lithium disilicate, petalite, and lithium monosilicate. Properly increasing the content of SiO2 can increase the stability and mechanical strength of the glass, but excessive SiO2 will increase the viscosity of the substrate glass, making it more difficult to melt the glass, thereby reducing the formability of the substrate glass. In some embodiments, the mass percentage of SiO2 in the composition of the substrate glass or the composition of the microcrystalline glass can be 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%,
[0164] 73%, 74%, 75%, 7.11%, 7.4%, 7.6% or 10.57%, or it can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the microcrystalline glass with the required performance of the present application can be obtained.
[0165] As an intermediate oxide, Al2O3 can improve the forming ability of glass, reduce the crystallization tendency of glass, improve the chemical stability, thermal stability, mechanical strength, hardness and heat resistance of glass, and to a certain extent, promote the exchange of ions in the chemical strengthening process, but excessive Al2O3 will increase the viscosity of glass. In some embodiments, in the composition of the substrate glass or the composition of the microcrystalline glass, the mass percentage of Al2O3 can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5% or 15%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the required performance of the present application can be obtained.
[0166] P2O5 is a glass-forming oxide and is also commonly used as a nucleating agent in glass-ceramics. In some embodiments, the mass percentage of P2O5 in the composition of the substrate glass or the composition of the glass-ceramics can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 2.27%, 2.34% or 2.53% in terms of the mass percentage of the oxide, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the performance required by the present application can be obtained.
[0167] ZrO2 is an intermediate oxide in the formation of glass. An appropriate amount of ZrO2 can improve the chemical stability of glass, increase the hardness of glass, and the scratch and drop resistance of glass. At the same time, due to the high cation charge and strong field strength of ZrO2, it has a greater accumulation effect on the glass structure, and is also often used as a nucleating agent in microcrystalline glass. In some embodiments, in terms of the mass percentage of oxide, the mass percentage of ZrO2 in the composition of the substrate glass or the composition of the microcrystalline glass can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 3.8%, 5.32%, 5.65% or 6.39%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the performance required by the present application can be obtained.
[0168] Na2O, as one of the optional components, is a network exosome oxide. An appropriate amount of Na2O can provide free oxygen, improve the viscosity of the glass, promote the melting and clarification of the glass liquid, and also adjust the chemical strengthening rate. However, excessive Na2O will not only reduce the crystallinity of the microcrystalline glass, but also affect the chemical strengthening effect. In some embodiments, in terms of the mass percentage of oxides, the mass percentage of Na2O in the composition of the substrate glass or the composition of the microcrystalline glass can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 11%, 12%, 13%, 14%, 15%,
[0169] 0.88%, 2.06% or 3.36%, or it can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the required performance of the present application can be obtained.
[0170] K2O is an oxide outside the glass network and is an optional component. An appropriate amount of K2O can provide free oxygen to increase the oxygen-silicon ratio in the glass structure, but too much K2O will affect the network structure of the glass, affecting the optical properties, thermal stability, chemical stability, mechanical strength and weather resistance of the glass. In some embodiments, in terms of the mass percentage of oxides, in the composition of the substrate glass or the composition of the microcrystalline glass,
[0171] The mass percentage of K2O can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or 1.76%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the required properties of the present application can be obtained.
[0172] In the present application, Sb2O3 is an optional component and can be used as a clarifier for glass. In some embodiments, the mass percentage of Sb2O3 in the composition of the substrate glass or the composition of the microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1% by mass percentage of the oxide, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the performance required by the present application can be obtained.
[0173] SnO2 is an optional component and can be used as a clarifier for glass. In some embodiments, the mass percentage of SnO2 in the composition of the substrate glass or the composition of the microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the desired performance of the present application can be obtained.
[0174] CaO is an optional component of the network exosome oxide formed by glass. An appropriate amount of CaO helps to reduce the high temperature viscosity of glass and increase the density of glass, but excessive CaO will shorten the material properties of glass and increase its brittleness. In some embodiments, in terms of the mass percentage of oxide, the mass percentage of CaO in the composition of the substrate glass or the composition of the microcrystalline glass can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3% or 0.88%, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the required performance of the present application can be obtained.
[0175] As an essential component, Li2O is a network exo-oxide formed by glass. It can not only improve the viscosity of glass and promote the melting and clarification of glass liquid, but also is one of the main components for forming lithium phosphate, spodumene, lithium monosilicate, lithium disilicate, and petalite crystals. At the same time, Li2O can also provide alkali metal lithium ions for ion exchange with large radius ions in the molten salt bath, which is an important factor affecting the stress level that can be obtained by microcrystalline glass. In some embodiments, the mass percentage of Li2O in the composition of the substrate glass or the composition of the microcrystalline glass can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77 7%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 10.78%, 11.17%, 11.2% or 15.21%, or it can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the microcrystalline glass with the required performance of the present application can be obtained.
[0176] B2O3 is an optional component. An appropriate amount of B2O3 can be used as a flux and / or softener to help improve the molding and hot bending effects of the glass. However, excessive B2O3 will cause the crystallization process to be uncontrollable, resulting in the deterioration of the optical properties of the microcrystalline glass. In some embodiments, the mass percentage of B2O3 in the composition of the substrate glass or the composition of the microcrystalline glass can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 0.2%, 0.35%, 0.6% or 2.05%, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the performance required by the present application can be obtained.
[0177] Y2O3 is an optional component. An appropriate amount of Y2O3 helps to increase the density of the microcrystalline glass and increase its Young's modulus, but it may also increase the refractive index of the microcrystalline glass and reduce the optical properties of the microcrystalline glass. In some embodiments, the mass percentage of Y2O3 in the composition of the substrate glass or the composition of the microcrystalline glass can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or 2.78% in terms of the mass percentage of the oxide, or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the performance required by the present application can be obtained.
[0178] MgO is an optional component. In some embodiments, the mass percentage of MgO in the composition of the substrate glass or the composition of the microcrystalline glass can be 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or 0.49% as measured by the mass percentage of the oxide. Or it can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the required performance of the present application can be obtained.
[0179] In some embodiments of the present application, the microcrystalline glass is transparent in the visible light wavelength range. Preferably, for light with a wavelength of 550nm, the transmittance of the microcrystalline glass is ≥85%, preferably, the transmittance is ≥90%. Microcrystalline glass that meets this transmittance can ensure good display and transparency effects, and is suitable for use in electronic device display screens that require display effects. It should be understood that the transmittance of microcrystalline glass is usually related to its thickness. Generally, the smaller the thickness, the greater the transmittance.
[0180] In some embodiments, for 550nm wavelength light, the transmittance of the microcrystalline glass can be 85%, 90%, 91%, 92%, 90.6%, 90.7% or 90.9%, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass with the performance required by the present application can be obtained.
[0181] In some embodiments of the present application, the density of the microcrystalline glass is 2.4 g / cm 3 ~2.7g / cm 3 , preferably 2.5 g / cm 3 ~2.6g / cm 3 In some embodiments, the density of the glass-ceramic can be 2.4 g / cm 3 , 2.42g / cm 3 , 2.44g / cm 3 , 2.46g / cm 3 , 2.48g / cm 3 , 2.51g / cm 3 , 2.52g / cm 3 , 2.53g / cm 3 , 2.54g / cm 3 , 2.55g / cm 3 , 2.56g / cm 3 , 2.57g / cm 3 , 2.58g / cm3 , 2.59g / cm 3 , 2.60g / cm 3 , 2.61g / cm 3 , 2.62g / cm 3 , 2.63g / cm 3 , 2.64g / cm 3 , 2.65g / cm 3 , 2.67g / cm 3 or 2.7 g / cm 3 , or it can be a value within the numerical range formed by any two of the above specific values as endpoints, as long as the microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass with the performance required by the present application can be obtained.
[0182] In some embodiments of the present application, the refractive index of the glass-ceramics is ≤1.60, preferably, the refractive index is 1.5-1.6. In some embodiments, the refractive index of the glass-ceramics can be 1.5, 1.51, 1.52, 1.53, 1.54, 1.55, 1.56, 1.57, 1.58, 1.59 or 1.60, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the required performance of the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics with the required performance of the present application can be obtained.
[0183] In some embodiments of the present application, the Poisson's ratio of the glass-ceramics is 0.2 to 0.3. In some embodiments, the Poisson's ratio of the glass-ceramics can be 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29 or 0.3, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics with the performance required by the present application can be obtained.
[0184] In some embodiments of the present application, the surface of the microcrystalline glass has a compressive stress layer and the interior has a tensile stress layer. By chemically strengthening the ultra-thin microcrystalline glass with a surface roughness as small as possible and a specific edge shape chamfer structure, the bending performance of the ultra-thin microcrystalline glass can be improved to a higher range, thereby significantly improving the bending performance and bending life of the ultra-thin microcrystalline glass.
[0185] It should be understood that chemical strengthening treatment can be used to form compressive stress layers and tensile stress layers in glass-ceramics. In the present application, when the glass-ceramics are chemically strengthened, the composition at the center of the glass-ceramics is the same or substantially the same as the composition of the glass-ceramics. Compared to the glass-ceramics before chemical strengthening treatment, the composition at the surface of the glass-ceramics product after chemical strengthening treatment may be different from the composition of the glass-ceramics before chemical strengthening treatment. This is because ion exchange occurs during the chemical strengthening process. During ion exchange, a type of alkali metal ion (for example, Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced. However, in an embodiment, the glass composition and phase assembly at the depth or thickness center or near the depth or thickness center of the microcrystalline glass product will still have the composition and phase assembly of the newly formed microcrystalline glass. That is to say, in the present application, after the microcrystalline glass is chemically strengthened, the composition (e.g., the composition of the tensile stress layer) and phase assembly at the center of the microcrystalline glass are the same or substantially the same as those of the microcrystalline glass that has not been chemically strengthened.
[0186] In some embodiments of the present application, the glass-ceramics may be 2D, 2.5D, 3D or special-shaped. In some embodiments of the present application, the glass-ceramics may be of equal thickness or unequal thickness. Those skilled in the art may make a choice according to their needs. Here, "unequal thickness" means that the glass-ceramics contains at least two parts of different thicknesses.
[0187] In some embodiments of the present application, the static limit bending radius R of the microcrystalline glass is 极限 Satisfy R 极限 ≤0.1492e Et / 1.40622 +0.0038E, where e is the natural base, E is the Young's modulus of the glass-ceramics, in GPa, and t is the thickness of the glass-ceramics, in mm. In some embodiments, the static limit bending radius R of the glass-ceramics is 极限 (mm)≤R2.0, preferably ≤R1.5. In some embodiments, the static limit bending radius R of the microcrystalline glass is 极限 (mm) is R2.0, R1.9, R1.8, R1.7, R1.6 or R1.5, or can be a value within a numerical range consisting of any two of the above specific values as endpoints, as long as the microcrystalline glass with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the microcrystalline glass with the performance required by the present application can be obtained.
[0188] In some embodiments of the present application, a bending life test is performed on the glass-ceramics. When the bending radius of the glass-ceramics is 1.346Et / 2, the number of dynamic bending times of the glass-ceramics is ≥50,000 times, wherein E is the Young's modulus of the glass-ceramics in GPa, and t is the thickness of the glass-ceramics in mm. In some embodiments, a bending life test is performed on the glass-ceramics. When the bending radius of the glass-ceramics is R2.0, the number of dynamic bending times of the glass-ceramics is ≥50,000 times. In some embodiments, the number of dynamic bending times is ≥50,000, and the bending radius of the glass-ceramics can be R2.0, R1.9, R1.8 or R1.7, or can be a value within the numerical range consisting of any two of the above specific values as endpoints, as long as the glass-ceramics with the performance required by the present application can be obtained. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the glass-ceramics with the performance required by the present application can be obtained.
[0189] In the present application, the smaller the measured static limit bending radius Rlimit and / or the greater the number of dynamic bending times, the better the bending performance of the microcrystalline glass.
[0190] In some embodiments of the present application, a coating or a stacked layer may be provided on at least one main surface of the glass-ceramic according to application requirements, including a coating layer or a stacked layer of an organic or inorganic material.
[0191] After introducing the morphology, composition, crystal phase structure, etc. of microcrystalline glass, the preparation method of microcrystalline glass is introduced in detail below.
[0192] In the present application, the preparation process of microcrystalline glass mainly includes: a process of obtaining a microcrystalline glass substrate and a process of processing the microcrystalline glass substrate to obtain microcrystalline glass with a specific surface roughness and a specific chamfer structure.
[0193] In the present application, the microcrystalline glass substrate can be obtained by purchase or by production.
[0194] For example, a microcrystalline glass substrate may be obtained through production, and the production of the microcrystalline glass substrate may include but is not limited to the following processes: a preparation process of a substrate glass and a heat treatment process of the substrate glass.
[0195] In the present application, the substrate glass can be prepared by a molding method in the prior art, and the present application has no limitation on this. For example, the molding method of the substrate glass can include but is not limited to float, overflow, rolling or casting processes. For example, the substrate glass can be obtained by uniformly mixing the components according to the formula, melting and molding, cooling and annealing.
[0196] Exemplarily, each raw material (industrial conventional raw material) is configured according to the formula ratio, a clarifier is added, and then mixed for a period of time to obtain a uniform raw material mixture. The raw material mixture is placed in a platinum crucible, a platinum rhodium crucible or a furnace, heated to 1450°C to 1700°C, preferably kept warm for 5 hours or more under the melting temperature condition, and then poured into a molding mold for cooling and molding, preferably cooled to about 900°C, and then placed in an annealing furnace for annealing treatment, preferably the annealing temperature is 450°C to 650°C, and the annealing time is preferably 10 to 48 hours, and then cooled to room temperature with the furnace to obtain the substrate glass. Those skilled in the art can select the type and amount of clarifier according to demand, and they do not need to pay creative labor. Further, the clarifier may include but is not limited to one or more of sodium chloride, tin oxide, antimony oxide or arsenic oxide, and the amount of clarifier added may be 0-1wt% of the total amount of each raw material.
[0197] In some embodiments of the present application, the heat treatment process of the substrate glass may include a nucleation treatment and / or a crystallization treatment, preferably a nucleation treatment and a crystallization treatment. In some embodiments of the present application, in order to obtain the desired physical and chemical properties of the microcrystalline glass, when the substrate glass is heat treated, a one-step heat treatment may be performed, or two-step or more-step heat treatment may be performed. If a one-step heat treatment is performed, it means that the nucleation treatment (i.e., nucleation treatment) is not performed separately, and a one-step heating is performed directly, and nucleation and crystal growth are performed at a temperature reached in the one-step heating process, which can be understood as directly performing a crystallization treatment. If a two-step heat treatment is performed, it means that a two-step heating process is performed, including but not limited to the following methods, a first step of nucleation treatment, and a second step of crystallization treatment.
[0198] In some embodiments of the present application, in order to precipitate the desired target crystalline phase in the microcrystalline glass substrate and obtain the desired physical and chemical properties, the substrate glass is subjected to nucleation treatment and crystallization treatment in sequence. Furthermore, when performing the nucleation treatment, the nucleation temperature can be 500-700°C, and the nucleation time can be 10-1440 min; when performing the crystallization treatment, the crystallization temperature can be 600-800°C, and the crystallization time can be 5-1440 min. During the heat treatment process of the nucleation treatment and the crystallization treatment, it is preferred to control the heating rate to be 5-20°C / min, more preferably the heating rate to be 10°C / min, and the cooling rate can be 0.1°C / min-3°C / min.
[0199] In the present application, after heat treatment, those skilled in the art may also perform other conventional steps to obtain a microcrystalline glass sample that meets the required specifications or requirements, for example, shaping treatment, cutting treatment (e.g., cutting using a multi-wire cutting machine), CNC machining (computer numerical control, i.e., CNC machine tools), thinning treatment, chamfering treatment or polishing treatment and the like.
[0200] In the present application, the process of processing a microcrystalline glass substrate to obtain a microcrystalline glass with a specific surface roughness and a specific chamfer structure includes but is not limited to the following steps: (1) thinning the microcrystalline glass substrate to obtain a microcrystalline glass primary product; (2) edge processing the obtained microcrystalline glass primary product so that the side surface of the microcrystalline glass forms an arc-shaped chamfer to obtain a microcrystalline glass with a chamfer structure, and the microcrystalline glass with a chamfer satisfies: the surface roughness Ra of the main surface is ≤150nm, a coordinate system is established on a cross section perpendicular to the side surface along the thickness direction, the symmetry axis of the two main surfaces of the microcrystalline glass is taken as the x-axis, and the straight line passing through the chamfer starting point on the main surface and perpendicular to the x-axis is taken as the y-axis, and the edge curve of the chamfer satisfies the following relationship:
[0201]
[0202] Wherein, k satisfies 0.36≤k≤3.52, preferably, 0.36≤k≤3, and more preferably, 0.36≤k≤2.5, and t is the thickness of the microcrystalline glass, in mm.
[0203] In some embodiments of the present application, the thickness of the microcrystalline glass substrate to be thinned is ≤0.6 mm, and the difference between the maximum thickness and the minimum thickness of the microcrystalline glass substrate TTV is ≤3 μm. The smaller the thickness of the microcrystalline glass substrate and / or the smaller the difference between the maximum thickness and the minimum thickness TTV, the more uniform the thickness of the microcrystalline glass product obtained after the thinning process can be guaranteed, and the risk of fragmentation during the thinning process can be reduced, thereby improving the thinning efficiency.
[0204] In some embodiments of the present application, the thickness of the primary glass-ceramics product is ≤0.2 mm, preferably 0.02 mm to 0.2 mm, more preferably 0.02 mm to 0.1 mm, and more preferably 0.02 mm to 0.05 mm.
[0205] In some embodiments of the present application, the thinning process may be: placing the microcrystalline glass substrate in a top-spray or immersion chemical etcher, and etching and thinning the microcrystalline glass substrate with an etching solution, wherein the etching solution includes one or more acids selected from hydrofluoric acid, nitric acid, sulfuric acid, and hydrochloric acid. For example, by mass percentage, the etching solution used in the microcrystalline glass thinning process includes 1% to 10% hydrofluoric acid, 5% to 10% nitric acid, 0% to 5% sulfuric acid, 0% to 5% hydrochloric acid, and water, and the etching temperature is 20 to 50°C. After etching for 5 to 200 minutes, a microcrystalline glass of a specified thickness is obtained. The type of crystal phase and crystallinity of the microcrystalline glass will affect its acid resistance, so different microcrystalline glasses have different etching times under the same etching solution formula, but the etching time is to meet the thickness requirements of the microcrystalline glass and does not affect the actual effect of the product.
[0206] In some embodiments of the present application, the edge treatment includes chemically etching the primary microcrystalline glass product with an etching solution. For example, the primary microcrystalline glass product can be first soaked in water, and then the edge of the primary microcrystalline glass product is chemically etched with an etching solution containing an acid or alkali, so that its edge forms an arc shape. In the present application, the etching solution for edge treatment preferably includes one or more of hydrofluoric acid, nitric acid, sulfuric acid, and hydrochloric acid. More preferably, the composition of the etching solution includes, by mass percentage, 1% to 10% hydrofluoric acid, 1% to 10% nitric acid, 0% to 5% sulfuric acid and water. Preferably, during the etching treatment, the etching temperature is 20°C to 50°C, and the etching time is 60s to 3600s.
[0207] In some embodiments of the present application, before edge treatment, the step of coating the primary glass-ceramics product is also included to form an acid-resistant coating on the main surface of the primary glass-ceramics product;
[0208] Those skilled in the art should be aware that in order to accurately chamfer the edges, before edge processing, the step of coating the primary microcrystalline glass product is also included to form an acid-resistant coating on the main surface of the primary microcrystalline glass product. For example, the primary microcrystalline glass product can be coated with ink, and the ink coated with ink has strong acid resistance. Subsequently, the primary microcrystalline glass product with ink is laser cut to obtain microcrystalline glass with ink on both sides.
[0209] Those skilled in the art should know that in order to remove the ink, after the edge treatment, the step of demolding the microcrystalline glass with a chamfered structure is also included, and the demolding and slicing are performed. For example, the microcrystalline glass with the treated edges is placed in a deinking tank for demolding. The microcrystalline glass is preferably demolded using a demolding agent. The demolding agent preferably includes one or more of sodium hydroxide, sodium bicarbonate, and sodium carbonate. Preferably, the composition of the demolding agent includes 1-20% sodium hydroxide, 0%-20% sodium bicarbonate, 0%-20% sodium carbonate and water in mass percentage. The preferred demolding treatment temperature is 50°C to 90°C, and the preferred demolding treatment time is 1min to 120min. After the demolding treatment, the microcrystalline glass is taken out.
[0210] In some embodiments of the present application, after the edge treatment, the obtained microcrystalline glass with a chamfered structure is subjected to a chemical strengthening treatment to form a compressive stress layer on the surface of the microcrystalline glass. Preferably, the salt bath composition for chemical strengthening treatment includes 0.01-0.30wt% lithium salt (one of lithium nitrate and lithium sulfate) and 1-99wt% sodium salt (one of sodium nitrate, sodium sulfate and sodium carbonate) and 1-99wt% potassium salt (one of potassium nitrate, potassium sulfate and potassium carbonate). The preferred chemical strengthening treatment salt bath temperature is 370℃~550℃, and the preferred chemical strengthening treatment time is 5min~240min. In the present application, the chemical strengthening treatment forms an ion exchange layer on the surface of the microcrystalline glass, and a certain compressive stress is generated on the surface to form a compressive stress layer. When the microcrystalline glass is bent, the compressive stress generated on the surface will first offset the force on the surface, that is, the formation of the surface compressive stress layer is conducive to improving the bending strength of the microcrystalline glass. At the same time, the compressive stress layer formed by the chemical strengthening treatment can effectively eliminate or inhibit the further expansion of microcracks, thereby helping to improve the ability of microcrystalline glass to resist external forces and enhance the bending performance of microcrystalline glass.
[0211] In the present application, chemical strengthening treatment, namely ion exchange method, is carried out by immersing the microcrystalline glass in a molten salt bath so that the alkali metal ions with smaller ion radius in the microcrystalline glass are exchanged with the alkali metal ions with larger ion radius in the molten salt bath, thereby forming a compressive stress layer on the surface of the microcrystalline glass and a tensile stress layer inside the microcrystalline glass, thereby obtaining microcrystalline glass with better mechanical properties (in order to distinguish it from chemically strengthened microcrystalline glass, the strengthened microcrystalline glass can be referred to as chemically strengthened microcrystalline glass).
[0212] In some embodiments of the present application, it is also included that after the chemical strengthening treatment, the surface of the obtained microcrystalline glass with a compressive stress layer is subjected to surface strengthening treatment. It is preferred to use chemical polishing to perform surface strengthening treatment. For example, the microcrystalline glass with a compressive stress layer is preferably placed in an etching solution for surface strengthening treatment. The etching solution preferably contains one or more of hydrofluoric acid, nitric acid, hydrochloric acid, and sulfuric acid. Preferably, the composition of the etching solution includes 0.1% to 2% hydrofluoric acid, 0.5 to 2% nitric acid, 0% to 1% hydrochloric acid, 0 to 1% sulfuric acid and water by mass percentage. The etching time is preferably 60s to 1200s, and the etching temperature is preferably 20°C to 50°C. In the present application, chemical polishing of the surface of the microcrystalline glass with a compressive stress layer can improve the uniformity of the surface of the microcrystalline glass and passivate the microcracks on the surface of the microcrystalline glass, thereby facilitating the improvement of the ability of the microcrystalline glass to resist external forces and the improvement of the bending performance of the microcrystalline glass.
[0213] It should be understood that, in the present application, the crystallinity of the microcrystalline glass does not change significantly after chemical strengthening treatment, that is, the crystallinity of the microcrystalline glass is similar to or substantially the same as the crystallinity of the chemically strengthened microcrystalline glass.
[0214] It should be understood that in the present application, the optical properties of the microcrystalline glass do not change significantly after chemical strengthening treatment, that is, the transmittance of the microcrystalline glass is similar to or basically the same as the transmittance of the chemically strengthened microcrystalline glass.
[0215] It should be understood that in the present application, the Young's modulus of the microcrystalline glass does not decrease after chemical strengthening treatment, that is, when the Young's modulus of the microcrystalline glass is greater than 80 GPa, the Young's modulus of the chemically strengthened microcrystalline glass should also be greater than 80 GPa.
[0216] In some embodiments of the present application, the step of coating the microcrystalline glass after surface strength treatment may also be included to form a coating layer or a stacked layer of organic or inorganic material on at least one main surface of the microcrystalline glass, which is conducive to better application of the microcrystalline glass.
[0217] The microcrystalline glass with excellent performance provided by the present application can be used in flexible and foldable electronic devices, displays, sensors, semiconductor packages or thin-film batteries. For example, it can be used in the field of cover plates and substrates of flexible and foldable electronic devices, such as fragile sensors, fingerprint sensors, image sensors, display cover plates, screen protectors, curved displays, wearable devices or flexible electronic devices. Flexible substrates for holding or mounting components can also be used in, for example, the following application fields: display substrates or protective cover plates, fingerprint sensor cover plates, general sensor substrates or cover plates, cover glass of consumer electronic products, protective cover plates and other surfaces of displays, especially curved surfaces. It can also be used in the applications of display substrates and cover plates, fingerprint sensor module substrates or cover plates, semiconductor packages, thin-film battery substrates and cover plates and foldable displays. For example, it can be used as a coating for resistive screens, as well as consumable protective films for display screens, mobile phones, cameras, game device accessories, tablets, laptops, televisions, mirrors, windows, aviation windows, furniture and white goods.
[0218] The glass-ceramics with excellent performance provided in the present application can also be used to manufacture glass devices. The glass devices referred to here can be regular or irregular, and those skilled in the art can manufacture them according to requirements.
[0219] For example, the microcrystalline glass with excellent performance provided by the present application can be used to manufacture cover glass, and the cover glass can be a display cover, back cover or camera protection cover of an electronic device. For example, the microcrystalline glass with excellent performance provided by the present application can be used in electronic devices. Figure 6 and Figure 7 In an embodiment of the present application, an electronic device is provided, which may be an electronic product such as a mobile phone, a tablet computer, a smart wearable device, etc. The electronic device includes a housing 1 assembled on the outside of the electronic device, and components such as a circuit board and a battery located inside the housing 1. The housing 1 includes a display screen cover 11 assembled on the front side and a back cover 12 assembled on the back side. The display screen cover 11 is covered on the display module 4, wherein the display screen cover 11 and / or the back cover 12 are made of the aforementioned microcrystalline glass. In an embodiment of the present application, the display screen cover 11 and the back cover 12 may be entirely made of the aforementioned microcrystalline glass, or only partially made of the aforementioned microcrystalline glass. In an embodiment of the present application, the display screen may be a touch display screen, and the display screen cover 11 may be a protective cover provided on the touch display screen. In an embodiment of the present application, the back cover 12 may cover only the back side (and the side away from the display screen) of the electronic device, or may cover both the back side and the side frame of the electronic device. Optionally, the back cover 12 may cover all the side frames around the electronic device, or may cover part of the side frames.
[0220] In some implementation modes of the present application, Figure 7 As shown, the electronic device also includes a camera assembly 2 located inside the housing 1, and the housing 1 may include a camera protection cover 13, and the camera protection cover 13 is covered on the camera assembly 2 to protect the camera assembly 2, and the camera protection cover 13 may adopt the aforementioned microcrystalline glass. In the embodiment of the present application, the camera protection cover 13 may be partially made of the aforementioned microcrystalline glass, or may be entirely made of the aforementioned microcrystalline glass. In the embodiment of the present application, the setting position of the camera protection cover 13 is determined according to the setting position of the camera assembly 2, and may be located on the front side of the electronic device, or may be located on the back side of the electronic device. In some embodiments of the present application, the camera protection cover 13 may be a separate structure from the display screen cover 11 or the back cover 12. In other embodiments of the present application, the camera protection cover 13 may also be an integrated structure with the display screen cover 11 or the back cover 12.
[0221] In the embodiments of the present application, the display screen cover, back cover, and camera protection cover in the electronic device may be made of any one of the aforementioned microcrystalline glass, any two of the three may be made of the aforementioned microcrystalline glass, or all three may be made of the aforementioned microcrystalline glass.
[0222] In some embodiments of the present application, the display screen cover, back cover or camera protection cover in the electronic device can be 2D, 2.5D, 3D or special-shaped. In some embodiments of the present application, the display screen cover, back cover or camera protection cover in the electronic device can be of equal thickness or unequal thickness.
[0223] The technical solution of the present application is further described in detail below in conjunction with the embodiments. The embodiments of the present application described in detail below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application.
[0224] Example 1
[0225] 1. Preparation of substrate glass
[0226] The raw materials were prepared according to the proportions of the oxides in Table 1. The total mass of the prepared raw materials was 1000 g. The raw materials were then mixed with a V-type mixer at a speed of 25 r / min for more than 30 minutes to obtain a uniform raw material mixture.
[0227] The mixed raw material mixture is transferred to a platinum-rhodium crucible, and then melted in the platinum-rhodium crucible at 1500℃ for more than 5 hours, and then poured into a molding mold for molding and cooling. When it cools to about 900℃, it is placed in a 470℃ annealing furnace for annealing for 14 hours, and then cooled to room temperature with the furnace to obtain a base glass brick with a size of approximately 180mm*65mm*24mm.
[0228] 2. Preparation of glass-ceramics
[0229] The base glass brick is subjected to nucleation treatment and crystallization treatment in sequence to prepare a transparent micro-ceramic glass brick. The composition of the prepared micro-ceramic glass is the same as that of the base glass in terms of the mass percentage of oxides, as shown in Table 1.
[0230] In order to obtain the microcrystalline glass product of Example 1 of the present application, during the nucleation treatment, the temperature is increased to the nucleation temperature at a heating rate of 10°C / min, the nucleation temperature is 540°C, and the nucleation insulation time is 240min; during the crystallization treatment, the temperature is increased from the nucleation temperature to the crystallization temperature at a heating rate of 10°C / min, the crystallization temperature is 690°C, and the crystallization insulation time is 60min, and then the temperature is cooled to room temperature at a cooling rate of 1°C / min to obtain a microcrystalline glass sample brick. The nucleation insulation time here, i.e. the nucleation time, refers to the insulation time after the temperature is increased to the set nucleation temperature at the set heating rate. The crystallization insulation time here, i.e. the crystallization time, refers to the insulation time after the temperature is increased to the set crystallization temperature at the set heating rate.
[0231] 2. Glass-ceramic substrate processing:
[0232] The obtained glass-ceramic sample bricks are subjected to cold working treatments of cutting, CNC processing (the CNC instrument model used in this application is: RCG500S), and polishing in sequence, and a glass-ceramic substrate that meets the required specifications and requirements can be obtained. In the specific embodiments and comparative examples of this application, the glass-ceramic sample bricks are subjected to the aforementioned cold working treatment to produce a glass-ceramic substrate with a length and width of 50 mm×50 mm and a thickness of 0.50 mm.
[0233] The thickness of the microcrystalline glass substrate prepared in Example 1 is 0.5 mm, and the difference TTV between the maximum thickness and the minimum thickness of the microcrystalline glass substrate is 2 μm.
[0234] The test results of the microcrystalline glass substrate obtained in Example 1 are as follows:
[0235] The crystal phase composition, crystallinity, proportion of the main crystal phase in all crystal phases, average grain size, density, Poisson's ratio, refractive index, Young's modulus and transmittance (under 550nm wavelength light) of the microcrystalline glass substrate were tested respectively. The results are shown in Table 3.
[0236] 4. Thinning treatment:
[0237] The microcrystalline glass substrate is placed in a top-spray chemical etcher and chemically etched and thinned using an etching solution. The etching solution used for thinning the microcrystalline glass substrate includes 5% HF, 7% HNO3, 2% HCL, 3% H2SO4 and 83% H2O by mass percentage. The etching temperature is 24.6°C and the etching treatment is performed for 20 minutes to obtain a microcrystalline glass substrate with a thickness of 0.03 mm.
[0238] 5. Thin film screen printing:
[0239] The two main surfaces of the microcrystalline glass primary product are coated with ink using a scraper, and an ink layer with strong acid resistance is coated on the two main surfaces. The microcrystalline glass primary product with the ink layer is then laser cut to obtain a microcrystalline glass primary product with ink layers on both sides.
[0240] 6. Edge processing:
[0241] Place the double-sided microcrystalline glass product stack with ink layer into the etching tank, and use etching liquid to chemically etch the edges of the microcrystalline glass product so that the edges form arc-shaped chamfers. The etching liquid includes 2% HF, 3% HNO3 and water by mass percentage, the etching temperature is 25°C, and the etching is performed for 400s to obtain microcrystalline glass with an arc-shaped chamfer structure.
[0242] 7. De-filming and Slicing:
[0243] Place the edge-treated microcrystalline glass in a deinking tank and use a demolding agent to de-mold the microcrystalline glass. According to mass percentage, the demolding agent includes 10% sodium hydroxide and water, the demolding temperature is 70°C, the demolding time is 60 minutes, and then the microcrystalline glass is taken out in pieces. Since the purpose here is to remove the ink layer, the whole process can also be called a deinking process.
[0244] 8. Chemical strengthening:
[0245] The glass-ceramics after demolding treatment was placed in a salt bath (1% NaNO3+99% K NO3) at 390°C for chemical strengthening treatment for 15 minutes. After chemical strengthening treatment, the glass-ceramics sample was taken out and placed on the strengthening furnace body to slowly cool to room temperature, and then the salt wrapped on the surface of the glass-ceramics was washed off with clean water. After the glass-ceramics sample was dried, the chemically strengthened glass-ceramics was obtained.
[0246] 9. Surface strength treatment:
[0247] The chemically strengthened microcrystalline glass is placed in an etching solution for surface strengthening treatment. The etching solution for surface strengthening treatment includes 0.7% HF, 0.8% HNO3 and water by mass percentage. The etching time is 100s and the etching temperature is 24°C. After ultrasonic cleaning, the desired microcrystalline glass can be obtained.
[0248] The test results of the glass-ceramics obtained after the surface treatment of Example 1 are as follows:
[0249] The surface roughness, chamfer width a, chamfer height b, chamfer edge morphology, limit bending radius and bending life of the microcrystalline glass were tested respectively, and the ratio of the chamfer width a to the chamfer height b, the ratio of the chamfer width a to the microcrystalline glass thickness t were calculated, and the relationship / function satisfied by the edge curve of the chamfer was fitted. The results are shown in Table 3.
[0250] The morphology of the chamfer of the microcrystalline glass of Example 1 magnified 40 times is as follows: Figure 4 As shown in the figure, it can be seen that the chamfered edge of the microcrystalline glass is in an arc shape. Through fitting, it can be seen that the chamfered edge curve satisfies the relationship, The value of k is 0.36.
[0251] Example 2-Example 4
[0252] The above methods are respectively carried out with reference to Example 1, except that the glass composition, different process parameters and corresponding test results of each example are shown in Tables 1 to 4, respectively.
[0253] The surface morphology and roughness of the microcrystalline glass of Example 2 magnified 20 times are as follows: Figure 5 shown.
[0254] Comparative Example 1-Comparative Example 11
[0255] The above methods are respectively carried out with reference to Example 1, except that the glass composition, different process parameters and corresponding test results of each comparative example are shown in Tables 1 to 4, respectively.
[0256]
[0257]
[0258]
[0259]
[0260]
[0261]
[0262]
[0263]
[0264] It can be obtained from the embodiments and comparative examples of the above statements 1-Table 4 that, compared with the comparative example, the embodiment scheme of the present application is adopted, by making the surface roughness of the two main surfaces of the microcrystalline glass meet a specific range, and at the same time, during edge processing, the ultra-thin microcrystalline glass is formed into an arc chamfered structure with a specific edge shape, the size of the chamfer (such as width, height) and the thickness of the microcrystalline glass meet a specific relationship, the Young's modulus of the microcrystalline glass meets a specific range, and the microcrystalline glass meets a specific composition, which can significantly improve the bending performance of the ultra-thin microcrystalline glass obtained, make the ultimate bending radius of the ultra-thin microcrystalline glass obtained lower, and make the dynamic bending life of the ultra-thin microcrystalline glass longer. This shows that the specific surface roughness and specific chamfered structure of the ultra-thin microcrystalline glass of the present application are conducive to reducing the risk of breakage caused by edge stress concentration during the bending process, so that the microcrystalline glass has better bending performance.
[0265] However, in the schemes of Comparative Examples 1 to 11, the roughness and chamfer structure of the main surface of the ultra-thin microcrystalline glass obtained do not meet the specific requirements of the present application, such as, the surface roughness range required by the scheme of the present application is not met, and / or, the chamfer curve relationship required by the scheme of the present application is not met. Finally, the ultra-thin microcrystalline glass obtained in the schemes of each comparative example either has a large maximum bending radius and cannot meet the bending of smaller angles, or it is difficult to pass the 50,000 times dynamic bending test and cannot meet the bending life requirements.
[0266] For example, the surface roughness of the ultra-thin glass-ceramics prepared in Examples 1, 5, 6 and 10 exceeds the scope requirements of the technical solution of the present application. When the ultimate bending radius and bending life are finally tested, it is found that the ultimate bending radius of these glass-ceramics is greater than the embodiment of the present application, and in the bending life test process, these glass-ceramics still cannot pass the dynamic bending test of 50,000 times under the condition of a larger bending radius. The chamfered edge curves of the ultra-thin glass-ceramics prepared in Examples 2 to 4 and Examples 7 to 9 do not meet the specific function requirements of the solution of the present application. When the ultimate bending radius and bending life are finally tested, it is found that the ultimate bending radius of these glass-ceramics is also greater than the embodiment of the present application, and in the bending life test process, these glass-ceramics still cannot pass the dynamic bending test of 50,000 times under the condition of a larger bending radius. This shows that by making the surface roughness of the ultra-thin microcrystalline glass as small as possible and, at the same time, forming a chamfered structure with a specific edge shape during edge processing, it is beneficial to obtain an ultra-thin microcrystalline glass with better bending properties after chemical strengthening treatment.
[0267] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A glass-ceramic, characterized in that: The microcrystalline glass comprises a first main surface, a second main surface and at least one side surface connecting the first main surface and the second main surface; The surface roughness Ra of the first main surface and the second main surface satisfies: Ra≤150nm, preferably, Ra≤145nm, more preferably, Ra≤140nm; In the microcrystalline glass, at least one of the side surfaces has at least one chamfer, the edge of the chamfer is arc-shaped, a coordinate system is established in a cross section perpendicular to the side surface along the thickness direction, the symmetry axis of the two main surfaces of the microcrystalline glass is taken as the x-axis, and the straight line passing through the chamfer starting point on the main surface and perpendicular to the x-axis is taken as the y-axis, and the edge curve of the chamfer satisfies the following relationship: Wherein, k satisfies 0.36≤k≤3.52, preferably, 0.36≤k≤3, and more preferably, 0.36≤k≤2.5, and t is the thickness of the microcrystalline glass, in mm.
2. The glass-ceramic according to claim 1, characterized in that: The thickness t of the glass-ceramics is 0.02 mm to 0.2 mm, preferably 0.02 mm to 0.1 mm, and more preferably 0.02 mm to 0.05 mm; Preferably, in the microcrystalline glass, at least one of the side surfaces has a first chamfer facing the first main surface and a second chamfer facing the second main surface, and the first chamfer and the second chamfer are substantially symmetrical on both sides of the microcrystalline glass; Preferably, at least two side surfaces located in the length direction of the microcrystalline glass have the chamfers, and more preferably, four side surfaces of the microcrystalline glass have the chamfers.
3. The glass-ceramic according to any one of claims 1 to 2, characterized in that: The chamfer has a chamfer width a and a chamfer height b, and the chamfer width a and the chamfer height b of the chamfer satisfy: 1≤a / b≤20, preferably, 1≤a / b≤10, more preferably, 1.2≤a / b≤6, and / or, The chamfer width a of the chamfer and the thickness t of the microcrystalline glass satisfy: 0.6≤a / t≤1.5, preferably: 0.6≤a / t≤1.4, and more preferably, 0.6≤a / t≤1.
2.
4. The glass-ceramic according to any one of claims 1 to 3, characterized in that: The Young's modulus E of the microcrystalline glass is 80 GPa to 130 GPa, preferably 90 GPa to 120 GPa, and more preferably 95 GPa to 115 GPa.
5. The glass-ceramic according to any one of claims 1 to 4, characterized in that: Measured in percentage by mass of oxides, the components of the microcrystalline glass include: SiO2: 55%~75%, Al2O3: 5%~15%, P2O5: 1%~6%, ZrO2: 2%~10%, Na2O: 0~15%, K2O: 0~7%, Sb2O3: 0~1%, SnO2: 0~1%, CaO: 0~3%, Li2O: 5%~25%, B2O3: 0~5%, Y2O3: 0~5%, MgO: 0~5%.
6. The glass-ceramic according to any one of claims 1 to 5, characterized in that: The main crystalline phase of the microcrystalline glass comprises at least one of lithium phosphate, spodumene, lithium monosilicate, lithium disilicate, petalite, nepheline and β-quartz solid solution. Preferably, the main crystalline phase of the microcrystalline glass comprises at least one of lithium monosilicate, lithium disilicate and petalite; and / or, Among all the crystal phases of the glass-ceramics, the mass proportion of the main crystal phase is ≥50%; and / or, The crystallinity of the glass-ceramics is ≥10%, preferably ≥50%; and / or, The average grain size of the glass-ceramics is 6 nm to 100 nm, preferably 10 nm to 50 nm, and more preferably 15 nm to 30 nm.
7. The glass-ceramic according to any one of claims 1 to 6, characterized in that: The microcrystalline glass is transparent in the visible light wavelength range. Preferably, for light with a wavelength of 550 nm, the transmittance of the microcrystalline glass is ≥ 85%, preferably, the transmittance is ≥ 90%; and / or The density of the microcrystalline glass is 2.4 g / cm 3 ~2.7g / cm 3 , preferably 2.5 g / cm 3 ~2.6g / cm 3 and / or, The refractive index of the glass-ceramics is ≤1.6, preferably, the refractive index is 1.5 to 1.6; and / or The Poisson's ratio of the microcrystalline glass is 0.2 to 0.
3.
8. The glass-ceramic according to claim 1, characterized in that: The surface roughness Ra is 55nm to 140nm; and / or, In the relationship satisfied by the chamfered edge curve, the value of k is 0.36 to 2.
08.
9. The glass-ceramic according to claim 4, characterized in that: The Young's modulus E of the microcrystalline glass is 98.8 GPa to 110 GPa.
10. The glass-ceramic according to any one of claims 1 to 9, characterized in that: The microcrystalline glass has a compressive stress layer on the surface and a tensile stress layer inside.
11. The glass-ceramic according to claim 10, characterized in that: The static limit bending radius R of the microcrystalline glass 极限 Satisfy R 极限 ≤0.1492e Et / 1.40622 +0.0038E, wherein e is a natural base, E is the Young's modulus of the glass-ceramics, in GPa, and t is the thickness of the glass-ceramics, in mm; and / or, A bending life test is performed on the microcrystalline glass. The dynamic bending times of the microcrystalline glass are ≥50,000 times when the bending radius is 1.346Et / 2, wherein E is the Young's modulus of the microcrystalline glass, in GPa, and t is the thickness of the microcrystalline glass, in mm.
12. The glass-ceramics according to claim 10 or 11, characterized in that: The static limit bending radius R of the microcrystalline glass 极限 (mm)≤R2.0, preferably ≤R1.5; and / or, A bending life test is performed on the microcrystalline glass. When the microcrystalline glass is bent at a bending radius of R2.0, the number of dynamic bending times is ≥50,000 times.
13. A method for preparing glass-ceramics according to any one of claims 1 to 12, characterized in that: The method comprises the following steps: Thinning the glass-ceramic substrate to obtain a primary glass-ceramic product; The obtained glass-ceramics primary product is edge-processed so that the side surface of the glass-ceramics forms a chamfer with an arc-shaped edge, and a glass-ceramics with a chamfered structure is obtained. The glass-ceramics with a chamfer meets the following requirements: the surface roughness Ra of the main surface is ≤150nm, a coordinate system is established in a cross section perpendicular to the side surface along the thickness direction, the symmetry axis of the two main surfaces of the glass-ceramics is taken as the x-axis, and a straight line passing through the chamfer starting point on the main surface and perpendicular to the x-axis is taken as the y-axis, and the edge curve of the chamfer meets the following relationship: Wherein, k satisfies 0.36≤k≤3.52, preferably, 0.36≤k≤3, and more preferably, 0.36≤k≤2.5, and t is the thickness of the microcrystalline glass, in mm.
14. The method according to claim 13, characterized in that The thickness of the microcrystalline glass substrate is ≤0.6 mm, the difference between the maximum thickness and the minimum thickness of the microcrystalline glass substrate TTV is ≤3 μm, and the Young's modulus of the microcrystalline glass substrate is preferably 80 GPa to 130 GPa; And / or, the thickness of the primary glass-ceramics product is ≤0.2 mm, preferably 0.02 mm to 0.2 mm, more preferably 0.02 mm to 0.1 mm, and more preferably 0.02 mm to 0.05 mm.
15. The method according to any one of claims 13 to 14, characterized in that The method further comprises, after the edge treatment, performing a chemical strengthening treatment on the obtained microcrystalline glass with a chamfered structure, so that a compressive stress layer is formed on the surface of the microcrystalline glass; Preferably, the method further comprises, after the chemical strengthening treatment, performing surface strengthening treatment on the obtained microcrystalline glass having a compressive stress layer on the surface.
16. The method according to any one of claims 13 to 15, characterized in that The edge treatment includes chemically etching the initial microcrystalline glass product using an etching solution. Preferably, the etching solution includes one or more of hydrofluoric acid, nitric acid, sulfuric acid, and hydrochloric acid. More preferably, the etching solution is composed of 1% to 10% hydrofluoric acid, 1% to 10% nitric acid, 0% to 5% sulfuric acid and water in mass percentage. Preferably, during the etching treatment, the etching temperature is 20°C to 50°C, and the etching time is 60s to 3600s.
17. The method according to any one of claims 13 to 16, characterized in that Before edge treatment, the method further includes a step of coating the primary glass-ceramic product to form an acid-resistant coating on the main surface of the primary glass-ceramic product; After edge processing, the method also includes a step of stripping the microcrystalline glass with a chamfered structure.
18. A cover glass, characterized in that: The cover glass comprises the microcrystalline glass according to any one of claims 1 to 12 or the microcrystalline glass prepared by the method according to any one of claims 13 to 17.
19. An electronic device, characterized in that: The electronic device comprises the glass-ceramic according to any one of claims 1 to 12 or the glass-ceramic prepared by the method according to any one of claims 13 to 17.
20. The electronic device according to claim 19, characterized in that: The electronic device includes a housing assembled on the outside of the electronic device, wherein the housing includes the microcrystalline glass according to any one of claims 1 to 12 or the microcrystalline glass prepared by the method according to any one of claims 13 to 17.
21. The electronic device according to claim 20, characterized in that: The housing includes a display cover assembled on the front side of the electronic device, and the display cover includes the microcrystalline glass according to any one of claims 1 to 12 or the microcrystalline glass prepared by the method according to any one of claims 13 to 17.
22. The electronic device according to claim 19, characterized in that: The electronic device includes a foldable electronic device, a display, a sensor, a semiconductor package or a thin film battery. Preferably, the sensor includes a fragile sensor, a fingerprint sensor or an image sensor. Preferably, the microcrystalline glass is applied to a substrate or a cover of an electronic device.
Citation Information
Cited By
Antireflective glass ceramic articles and methods of making the same
WO2026183080A1
